1983
DOI: 10.1111/j.1600-0447.1983.tb07005.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological reactions to edentulousness and treatment with jawbone‐anchored bridges

Abstract: Total edentulousness can lead to chewing problems as well as to feelings of insecurity and inferiority and considerable psycho-social problems. For many people a conventional removable denture is unsatisfactory. A new method - osseointegration - involves a titanium screw being operated into the jawbone and the attachment of a fixed bridge. In a controlled study, 26 patients were examined pre- and postoperatively 3 months and then 2 years after the insertion of a jawbone-anchored bridge. The majority of them st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
53
0
9

Year Published

1986
1986
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 5 publications
5
53
0
9
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12] The Brånemark Novum concept was first developed in 1999 for the purpose of cost reduction. This concept involves the installation of only 3 implants in the mandibular interforaminal region and provides a fixed denture using prefabricated components.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12] The Brånemark Novum concept was first developed in 1999 for the purpose of cost reduction. This concept involves the installation of only 3 implants in the mandibular interforaminal region and provides a fixed denture using prefabricated components.…”
mentioning
confidence: 99%
“…These impairments can reduce quality of life, thus making edentulism an important public health issue. [1][2][3][4] Dependence on removable dentures is a reality for millions of people worldwide, but the cost remains an issue for many. 1 For this reason, optimization of the Brånemark protocol has been proposed.…”
mentioning
confidence: 99%
“…Tooth loss and the wearing of dentures may constitute serious psycho-social problems (1)(2)(3)(4)(5), yet the value of teeth and the severity of dental problems have received lower rank compared with other bodily parts, individual health, psychological and material problems (6)(7)(8). It is also accepted that life-stress which requires readjustment may be associated with the onset and extent of illness through hormonal and immune system changes (for review, see [9][10][11][12].…”
mentioning
confidence: 99%
“…Most published studies have only reported patient satisfaction with treatment outcome. [7][8][9] Assessment of patient expectation, in conjunction with a comprehensive clinical and radiological evaluation, is an essential part of the pre-treatment process. Comprehensive clinical assessment alone may not determine appropriate treatment need.…”
Section: Research Prosthetic Dentistrymentioning
confidence: 99%